One-Dimensional Residual Convolutional Autoencoder Based Feature Learning for Gearbox Fault Diagnosis - Yu, Jianbo; Zhou, Xingkang (IEEE transactions on industrial informatics, 2020)
Vibration signals are generally utilized for machinery fault diagnosis to perform timely maintenance and then reduce losses. Thus, the feature extraction on one-dimensional vibration signals often determines accuracy of those fault diagnosis models. These typical deep neural networks (DNNs), e.g., convolutional neural networks (CNNs), perform well in feature learning and have been applied in machine fault diagnosis. However, the supervised learning of CNN often requires a large amount of labeled images and thus limits its wide applications. In this article, a new DNN, one-dimensional residual convolutional autoencoder (1-DRCAE), is proposed for learning features from vibration signals directly in an unsupervised-learning way. First, 1-D convolutional autoencoder is proposed in 1-DRCAE for feature extraction. Second, a deconvolution operation is developed as decoder of 1-DRCAE to reconstruct the filtered signals. Third, residual learning is employed in 1-DRCAE to perform feature learning on 1-D vibration signals. The results show that 1-DRCAE has good signal denoising and feature extraction performance on vibration signals. It performs better on feature extraction than the typical DNNs, e.g., deep belief network, stacked autoencoders, and 1-D CNN.